Early childhood social-emotional development: an impact on a developing country - Rafiyya, Aishath; Kraiwanit, Tanpat; Limna, Pongsakorn; Sonsuphap, Rattaphong; Kasrisom, Arnon; Snongtaweeporn, Teeradej (International Journal of Evaluation and Research in Education (IJERE), 2024)
Early childhood social-emotional development profoundly shapes a child's well-being and future success. This study explains how legislative and regulatory strategies and policies regarding early childhood social-emotional development impact a developing country, specifically focusing on Thailand. Using a qualitative approach, in-depth interviews with 12 key informants in Thailand were conducted via purposive sampling. Data analysis involved documentary and content analyses. The study unveiled critical policies and strategies to support early childhood social-emotional development. These encompass early childhood education and care programs, enhanced professional development and support for educators, increased family engagement, accessible mental health support, and robust assessment and monitoring systems. Social-emotional development carries substantial economic implications, affecting education, workforce productivity, healthcare, crime rates, and overall societal well-being. Effective early childhood social-emotional development policies and strategies can boost children's well-being and future success. Therefore, investing in early childhood education and care programs, improving professional development for educators, fostering family involvement, offering mental health support, and implementing vigilant assessment and monitoring systems can empower young children to thrive in the short and long term.